2017
DOI: 10.1108/pm-01-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable property development by Southeast Asian property companies

Abstract: Purpose The purpose of this paper is to assess the sustainability levels in terms of sustainability practices amongst public-listed property companies in Southeast Asia. Design/methodology/approach The websites and annual reports for each company were assessed to determine the level of sustainability practices amongst property companies in Southeast Asia. Their sustainability strategies were then rigorously assessed by using a scorecard which assesses sustainability levels based on related issues. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Although the focus of the study is on the willingness to invest in green features, the survey was carried out in a more matured and developed market. Razali et al (2017) assessed the level of sustainability practices amongst the property companies in Southeast Asia. The study considered the websites and annual reports of the companies to assess the strategies based on related sustainability issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the focus of the study is on the willingness to invest in green features, the survey was carried out in a more matured and developed market. Razali et al (2017) assessed the level of sustainability practices amongst the property companies in Southeast Asia. The study considered the websites and annual reports of the companies to assess the strategies based on related sustainability issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of sustainability practices among public-listed property companies in Southeast Asia was also investigated [2]. The scope is limited to only five Southeast Asian countries, which are Singapore, Malaysia, Thailand, Indonesia and the Philippines.…”
Section: The Performance Evaluation Of Sustainable Property Developmementioning
confidence: 99%
“…Previous studies highlighted a few issues related to the performance of high-rise residential buildings and their environmental enhancement practices. It has been observed that the level of environmental enhancement practices among property companies in Southeast Asian countries, including Malaysia, 2 of 14 is very low due to lack of awareness about green practices [2]. Besides, the tenants or residents of the residential favour a good performance from property management companies in term of maintenance and facilities [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Content analysis is a very popular method among researchers in various fields due to the flexibility and systematised structure, being frequently applied in studying the non-financial information reported by entities (Belluci et al, 2019). In real estate research, this method was applied mostly to evaluate the sustainability levels in terms of sustainability practices amongst property companies (Laposa & Villupuram, 2010;Glass, 2012;Warren-Myers, 2012;Razali et al, 2017;Rashidfarokhi et al, 2018;Ionașcu et al, 2020).…”
Section: Picbe | 379mentioning
confidence: 99%